Baseline knowledge of potential pet toxins: a survey of pharmacists - Young, Natalie W. (Pharm Pract (Granada), 2017)
BACKGROUND: Consumer expenditures on their family pets are rapidly increasing, part of which can be attributed to prescription and OTC medications. In turn, community pharmacies are seeking and receiving an increased number of prescriptions for animals. Community pharmacists’ ability to safely care for animal patients is relatively unexplored. Human medications, their normal dosing and even medication excipients could be lethal in some animal patients. OBJECTIVE: The overarching objective of this study was to assess pharmacists’ baseline knowledge of potential pet poisons. METHODS: The sample consisted of licensed pharmacists registered with the North Carolina Board of Pharmacy. The Pet Toxins Survey (PTS), a survey consisting of 25 potential pet toxins, was administered during October and November 2015. Analyses consisted of calculating descriptive statics (including graphical summaries to test for normality), and inferential statistics (two-tailed t-tests and ANOVAs) to compare responses across demographic variables. RESULTS: A 6.3% response rate was obtained. After selecting either a dog or a cat to establish a frame of reference, participants in this study were able to correctly identify 15 of the 25 listed items as toxic to a pet (60% accuracy). Participants did not express adequate concern for the ingestion of several potential toxins. This includes potential excipients found in medication formulations such as xylitol, tea tree oil and caffeine. Female participants and those age 50 years and older were more likely to indicate concern for each potential toxin. There was no significant difference observed in responses based on the pharmacists’ work setting. CONCLUSIONS: The findings of this investigation suggest that pharmacists are deficient in their understanding of veterinary toxicology. Given the rise of community pharmacists caring for animal patients, it’s paramount that pharmacists be able to confidently distinguish potential pet toxins from non-toxins. It is also important that pharmacists receive a better understanding of what exposures require immediate action and what action should be taken.